MEASURING PROJECT PROFITABILITY: RATE OF RETURN OR PRESENT VALUE–A REPLY. - Bennett, J. W. (The Accounting Review, 1963)
The profitability of an investment proposal is dependent upon both the amount and the timing of its projected cash flows and that some means of establishing a basis for comparing cash flows over time is necessary in order to select the combination of investment proposals which is optimal. This is a complex problem but recent discussion has highlighted several points. Firstly, the measurement of the profitability of investments by means of the internal rate of return or marginal efficiency of capital suffers from the implicit assumption that the intermediate cash inflows produced by a project can be re-invested at a rate of return equal to the rate which is assessed for the initial project. As a result, it is necessary to introduce an independent discount rate to make comparable alternative projects. Secondly, for a corporation whose management wishes to act "in the interests of shareholders" and therefore aims to continually choose that financial position which maximizes its current stock prices and dividend.